Computation of Iron Losses Using FEM Model of Permanent Magnet Synchronous Motor - Gašparin, Lovrenc; Drobnič, Klemen; Fišer, Rastko (XXVIII. Symposium Electromagnetic Phenomena in Nonlinear Circuits (EPNC 2024): Conference Proceedings, 2025)
Accurate computation of iron losses in permanent magnet synchronous motors is a challenging task due to their nonlinear dependency on a motor’s instantaneous loading condition. In the proposed computational procedure, a finite element method (FEM) is used for calculations of magnetic flux density in each particular mesh element. Applying a fast Fourier transform (FFT), its harmonic content is determined, followed by iron loss density calculation independently for several significant harmonics in all mesh elements over the entire stator iron core of PMSM. The proposed procedure predicts iron losses significantly better than classic approach where sinusoidal magnetic flux density is assumed.